2021
DOI: 10.3389/fneur.2020.597737
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Early Electrocardiographic Abnormalities With Brain Injury Severity and Outcome in Severe Traumatic Brain Injury

Abstract: The aim of this study was to evaluate the frequency of electrocardiographic (ECG) abnormalities in the acute phase of severe traumatic brain injury (TBI) and the association with brain injury severity and outcome. In contrast to neurovascular diseases, sparse information is available on this issue. Data of adult patients with severe TBI admitted to the Intensive Care Unit (ICU) for intracranial pressure monitoring of a level-1 trauma center from 2002 till 2018 were analyzed. Patients with a cardiac history wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
7
0
3
Order By: Relevance
“…In a study on patients with SAH, 15% of patients with preoperative SAH developed STD [ 25 ]. ST-segment abnormalities were the most commonly reported ventricular repolarization disorders in TBI [ 26 ]. Even in the present study, STD occurred in 15.4% of the total patients with TBI, and the proportion of patients with STD with poor outcome was higher than that of patients with good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on patients with SAH, 15% of patients with preoperative SAH developed STD [ 25 ]. ST-segment abnormalities were the most commonly reported ventricular repolarization disorders in TBI [ 26 ]. Even in the present study, STD occurred in 15.4% of the total patients with TBI, and the proportion of patients with STD with poor outcome was higher than that of patients with good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the largest series of TBI patients, repolarization abnormalities were present in more than half of the patients. [ 23 ] Conduction disorders such as QT prolongation and arrhythmias were observed in 38% of patients. ECG abnormalities in SAH have been reported as between 49% and 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Electrocardiographic (ECG) changes, including morphological changes and rhythm disturbances, are common in TBI. Several studies have shown that ECG changes in patients with severe traumatic brain injury are associated with cardiac dysfunction and increased hospital mortality [50,64,71]. The most common ECG changes in patients with SAH and intracerebral hemorrhage (ICH) are repolarization abnormalities such as QT interval prolongation and morphology changes in ST-segment and T wave.…”
Section: Electrocardiographic (Ecg) Abnormalitiesmentioning
confidence: 99%
“…Arrhythmias are found more frequently in patients with diffuse brain injury. Even so, abnormalities on the ECG cannot pinpoint the location of the lesion in the brain [71]. A 12-lead ECG may be a helpful screening tool for isolated TBI patients with heart abnormalities prior to additional diagnostic investigations or therapies.…”
Section: Electrocardiographic (Ecg) Abnormalitiesmentioning
confidence: 99%